TEACHER’S EXPERIENCES IN TEACHING ENGLISH VOCABULARY TO DEAF SEVENTH GRADE STUDENTS - Nadila Tanjung; Siti Ismahani; Maryati Salmiah (Faculty of Tarbiyah nad Teacher Training, 2026)
This study aims to explore teacher’s experiences in teaching English vocabulary to seventh-grade deaf students, including the challenges the teacher face and the strategies the teacher employs. The study employs a descriptive qualitative approach. Data were collected through semi-structured in-depth interviews, non-participant observation, and documentation at a special education school in Medan, North Sumatra. The results indicate that despite lacking a background in English education, the teacher was able to develop pedagogical competencies independently and collaboratively over nearly two decades of teaching. Key challenges included the teacher’s limited academic proficiency in English, discrepancies between spelling and pronunciation, students’ poor retention of new vocabulary, and the diversity of students’ conditions. Teacher developed six adaptive strategies: the use of layered visual media and real objects, innovations in local phonetic spelling, SIBI/BISINDO sign language, systematic drills and repetition, individualized approaches, and creative project-based assessments. The innovation of local phonetic spelling is the most significant finding that has not been documented in previous literature and enriches the study of vocabulary teaching for deaf students in Indonesia.